2018
DOI: 10.1007/s12031-018-1035-0
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Preliminary Association of Ammonia Metabolism Genes GLS, CPS1, and GLUL with Risk of Alzheimer’s Disease, Major Depressive Disorder, and Type 2 Diabetes

Abstract: Ammonia is a toxic by-product of protein catabolism and is involved in changes in glutamate metabolism. Therefore, ammonia metabolism genes may link a range of diseases involving glutamate signaling such as Alzheimer's disease (AD), major depressive disorder (MDD), and type 2 diabetes (T2D). We analyzed data from a National Institute on Aging study with a family-based design to determine if 45 single nucleotide polymorphisms (SNPs) in glutaminase (GLS), carbamoyl phosphate synthetase 1 (CPS1), or glutamate-amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…Hou et al [ 53 ] and Olesen et al [ 54 ] demonstrated that DACT2 and KCND3 were found to be substantially related to atrial fibrillation. Ge and Concannon [ 55 ], Ferjeni et al [ 56 ], Anquetil et al [ 57 ], Glawe et al [ 58 ], Kawabata et al [ 59 ], Li et al [ 60 ], Buraczynska et al [ 61 ], Amini et al [ 62 ], Yang et al [ 63 ], Du Toit et al [ 64 ], Hirose et al [ 65 ], Zhang et al [ 66 ], Griffin et al [ 67 ], Zouidi et al [ 68 ], Trombetta et al [ 69 ], Alharbi et al [ 70 ], Ikarashi et al [ 71 ], Dharmadhikari et al [ 72 ], Sutton et al [ 73 ] and Deng et al [ 74 ] reported that UBASH3A, ZAP70, IDO1, ITGAL (integrin subunit alpha L). ITGB7, RASGRP1, CNR1, SLC2A1, SLC11A1, GPR84, SSTR5, KCNB1, GLUL (glutamate-ammonia ligase), BANK1, CACNA1E, LGR5, AQP3, SIGLEC7, SSTR2 and DNER (delta/notch like EGF repeat containing) could be an index for diabetes, but these genes might be responsible for progression of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al [ 53 ] and Olesen et al [ 54 ] demonstrated that DACT2 and KCND3 were found to be substantially related to atrial fibrillation. Ge and Concannon [ 55 ], Ferjeni et al [ 56 ], Anquetil et al [ 57 ], Glawe et al [ 58 ], Kawabata et al [ 59 ], Li et al [ 60 ], Buraczynska et al [ 61 ], Amini et al [ 62 ], Yang et al [ 63 ], Du Toit et al [ 64 ], Hirose et al [ 65 ], Zhang et al [ 66 ], Griffin et al [ 67 ], Zouidi et al [ 68 ], Trombetta et al [ 69 ], Alharbi et al [ 70 ], Ikarashi et al [ 71 ], Dharmadhikari et al [ 72 ], Sutton et al [ 73 ] and Deng et al [ 74 ] reported that UBASH3A, ZAP70, IDO1, ITGAL (integrin subunit alpha L). ITGB7, RASGRP1, CNR1, SLC2A1, SLC11A1, GPR84, SSTR5, KCNB1, GLUL (glutamate-ammonia ligase), BANK1, CACNA1E, LGR5, AQP3, SIGLEC7, SSTR2 and DNER (delta/notch like EGF repeat containing) could be an index for diabetes, but these genes might be responsible for progression of HF.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent identification of CPS1 variants correlating with increased plasma glycine and protective effects against atherosclerosis, in addition to the role of CPS1 in vascular signaling, this new model may also serve as a useful tool for the in‐depth study of the relationship of short‐ and long‐term cardiovascular effects and CPS1 enzymatic activity. Additional preliminary findings implicate CPS1 in Alzheimer's disease and other neurological disorders . These new studies, combined with the more established studies of CPS1 in cancer initiation and progression, make the murine model described here more broadly applicable beyond the field of urea cycle disorders.…”
Section: Discussionmentioning
confidence: 75%
“…Hou et al [44] and Olesen et al [45] demonstrated that DACT2 and KCND3 were found to be substantially related to atrial fibrillation. Ge and Concannon [46], Ferjeni et al [47], Anquetil et al [48], Glawe et al [49], Kawabata et al [50], Li et al [51], Buraczynska et al [52], Amini et al [53], Yang et al [54], Du Toit et al [55], Hirose et al [56], Zhang et al [57], Griffin et al [58], Zouidi et al [59], Trombetta et al [60], Alharbi et al [61], Ikarashi et al [62], Dharmadhikari et al [63], Sutton et al [64] and Deng et al [65] reported that UBASH3A, ZAP70, IDO1, ITGAL (integrin subunit alpha L). ITGB7, RASGRP1, CNR1, SLC2A1, SLC11A1, GPR84, SSTR5, KCNB1, GLUL (glutamate-ammonia ligase), BANK1, CACNA1E, LGR5, AQP3, SIGLEC7, SSTR2 and DNER (delta/notch like EGF repeat containing) could be an index for diabetes, but these genes might be responsible for progression of HF.…”
Section: Discussionmentioning
confidence: 99%